Growth of Spiny Lobster Panulirus homarus Fed with Moist Diet - Asep Ridwanudin; Varian Fahmi; Idham Sumarto Pratama, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Oxygen is a vital parameter in aquaculture activities. The decrease of dissolved oxygen levels in aquaculture media should be highly observed, since very low dissolved oxygen conditions (hypoxia) could negatively affect to the growth and survival of fish. Therefore, research on the condition of hypoxia is very important to be studied. This study was conducted in January-February 2013 at the Laboratorium of Fish Reproductive Physiology, Pukyong National University, South Korea to measure oxygen consumption in tilapia Oreochromis niloticus (total length: 14.2 ± 1.4 cm, weight: 31.3 ± 2.0 g) under normal conditions (normoxia) and hypoxia. Measurement was conducted using respirometer (dimension: 20 × 17,5 × 10 cm; volume: 3,5 L) every 10 minutes during four hours of observation. Experiment was conducted with three replications. The results showed that oxygen consumption of tilapia fingerlings in hypoxia conditions (12.09 ± 3.20 mg O2/kg/h) was lower than normoxia (35.67 ± 4.19 mg O2/kg/h) (P<0.01). Continuous hypoxic conditions could negatively affect fish movements, which could ultimately lead to mortality when dissolved oxygen levels are very low. Meanwhile, the results on determination of critical oxygen levels for tilapia showed a dissolved oxygen range of 1.9 ± 0.5 mg/L